Everyday Cognitive Control and Emotion Dysregulation in Young Adults With and Without ADHD: An Ecological Momentary Assessment Study. Issue 5 (March 2023) - Ben-Dor Cohen, Maayan; Maeir, Adina; Eldar, Eran; Nahum, Mor
Objective: This study examined the contribution of the temporal dynamics of two cognitive control mechanisms—inhibitory control (IC) and working memory (WM)—to emotion dysregulation (ED) in attention-deficit/hyperactivity disorder (ADHD) in ecological settings. Method: One hundred twenty-two participants (age 18–33 years; 60 with ADHD) reported their ED at baseline, followed by a 5-day ecological momentary assessment (EMA) study, with short behavioral IC and WM tasks performed five times/day. Results: For IC, mean and lability of performance over EMA significantly accounted for differences in ED but not baseline performance. For WM, both baseline and mean of EMA, but not EMA lability, accounted for ED variance. ADHD status further contributed to the explained variance of ED. Conclusions: Our results support the contribution of dynamic IC processes to ED in ADHD, in addition to WM performance level, and highlight the importance of dynamic and ecological investigation of different cognitive control components.